Muscle strength relation with hypertrophy indicators after 32 weeks of resistance training in postmenopausal women - V. Bonganha; R.M.O. Botelho; M.S. Conceição; M.P. Chacon-Mikahil; V.A. Madruga (Desafio Singular, 2010)
The aim of the present study was to evaluate muscle strength and hypertrophy indicators on increases of strength after 32 weeks of resistance training (RT), prescribed by the target of maximum repetitions in postmenopausal women. Fourteen physically inactive healthy women participated in this study. Three times a week they participated on RT. Body composition was measured by the technique of skinfold thickness. The hypertrophy indicators were represented by total and regional lean mass: arm muscle area (AMA) and thigh muscle area (TMA). Muscle strength was assessed through the test of one maximum repetition in exercises of horizontal leg press and arm curl. Statistical analysis was performed using the Friedman test. Results showed increases in muscle strength, AMA but not in TMA. Arm curl was strongly correlated to AMA. Leg press seemed to be associated to neural components of increases in strength. Muscle strength significantly increased after 32 weeks of RT regardless of increases in lean mass.